2012
DOI: 10.1016/j.pep.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein refolding protocol for the solubilization and purification of recombinant peptidoglycan-associated lipoprotein from Xylella fastidiosa overexpressed in Escherichia coli

Abstract: Xylella fastidiosa is a Gram-negative xylem-limited plant pathogenic bacterium responsible for several economically important crop diseases. Here, we present a novel and efficient protein refolding protocol for the solubilization and purification of recombinant X. fastidiosa peptidoglycan-associated lipoprotein (XfPal). Pal is an outer membrane protein that plays important roles in maintaining the integrity of the cell envelope and in bacterial pathogenicity. Because Pal has a highly hydrophobic N-terminal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
13
0
4
Order By: Relevance
“…[16] Also, the dialysis of the protein of interest in two times, as described above in the presence of glycerol and a concentration of EDTA that let any denatured protein -if present-effected by urea to renature (refolded) and retain its biological normal form again. [15] Ion-exchange is a largely used system for separating biomolecules according to differences in ionic charge, in this study we used primarily a weak anion exchange column, the DEAE Sepharose column for terminating the action of Enterokinase enzyme, by separating the Parathyroid hormone (target protein) after proteolysis of fusion protein by Enterokinase from the non-proteolysis fusion protein and the fusion partner (TrxA-His. Tag) of the proteolysis protein as well as all the proteolysis reaction products, this was carried out depending on proteins PI and the surrounding PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Also, the dialysis of the protein of interest in two times, as described above in the presence of glycerol and a concentration of EDTA that let any denatured protein -if present-effected by urea to renature (refolded) and retain its biological normal form again. [15] Ion-exchange is a largely used system for separating biomolecules according to differences in ionic charge, in this study we used primarily a weak anion exchange column, the DEAE Sepharose column for terminating the action of Enterokinase enzyme, by separating the Parathyroid hormone (target protein) after proteolysis of fusion protein by Enterokinase from the non-proteolysis fusion protein and the fusion partner (TrxA-His. Tag) of the proteolysis protein as well as all the proteolysis reaction products, this was carried out depending on proteins PI and the surrounding PH.…”
Section: Discussionmentioning
confidence: 99%
“…The binding and washing buffer used for HisLink TM Protein Purification consisted of 50 mM phosphate buffer (NaH 2 PO 4 ) PH = 8, 300 mM NaCl, 5 mM Imidazole and Up to 8 M Urea, while, the elution buffer contained the same component like binding and washing buffer in addition to 250 mM Imidazole. Then, the product of the HisLink TM Protein Purification system was dialyzed using dialysis tube as described by Santos et al [15] The recombinant protein was dialyzed in a buffer consisted of 50 mM phosphate buffer (NaH 2 PO 4 ), 100 mM NaCl, 0.1 Mm EDTA and 10% v/v glycerol (PH = 8). The volume of the dialysis buffer was primarily equal to 10X of sample volume (10 ml of sample was dialyzed in a 100 ml of dialysate).…”
Section: Cell Lysate Preparation and Expression Analysismentioning
confidence: 99%
“…The dynamics of inclusion body formation are such that there are typically a small number of inclusion bodies seeded by an incorrectly folded protein intermediate. Although various studies have suggested refolding strategies both in vivo (Zhao et al, 2012) and in vitro (Santos et al, 2012), the consensus is that it is critical to prevent inclusion body formation from ever occurring to maximize yield (Schein, 1989; Fink, 1998). …”
Section: Commentarymentioning
confidence: 99%
“…• C and with 100X from the same solution for 16h at 4 • C. [12] Treatment with Factor Xa: To remove His-tag from produced protein, factor Xa (Biolab, U.K.) was used by incubation for 6 h at 23…”
Section: Hs Gene Expression In Bl21(de3)mentioning
confidence: 99%